Analisis Kerusakan Jalan dan Peningkatannya di Jalan Lingkar Selatan dan Jalan Lingkar Barat Kota Jambi - Laksana, Tendy; Agustien, Melawaty; Kadarsa, Edi (Universitas Batanghari Jambi, 2025)
Road damage causes a road pavement to be incompatible with the original pavement shape, so that it can cause the road pavement to be damaged which affects the service life of the road. The South Ring Road of Jambi City and the West Ring Road of Jambi City are roads with a fairly high traffic volume with a class I arterial road type. This route is a route that is often used for the flow of goods transport in and out of Jambi City. This road damage causes the road to be unsafe and uncomfortable for motorists to pass. The South Ring Road of Jambi City has a road length of 9.12 km and the West Ring Road is 7.17 km long. The types of road damage that occur are potholes, cracks, grain detachment, peeling of the surface layer, wear. The calculation method used is the 'Bina Marga' method, PCI, and Asphalt Institute. The calculation results show that the assessment of road pavement damage includes 4 types of road damage, namely crocodile cracks, longitudinal cracks, transverse cracks, potholes with different levels of severity. Road damage assessment based on the 'Bina Marga' Method, Asphalt Institute Method, PCI Method on the South Ring Road section and the West Ring Road section of Jambi City obtained different road damage assessments and different maintenance handling sequences.